Hong Kong Med J 2020
DOI: 10.12809/hkmj208725
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological characteristics of COVID-19: a multicentre, retrospective, observational study

Abstract: Background: Multicentre cohort investigations of patients with coronavirus disease 2019 (COVID-19) have been limited. We investigated the clinical and chest computed tomography characteristics of patients with COVID-19 at the peak of the epidemic from multiple centres in China. Methods: We retrospectively analysed the epidemiologic, clinical, laboratory, and radiological characteristics of 189 patients with confirmed COVID-19 who were admitted to seven hospitals in four Chinese provinces from 18 January 2020 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…A recent study involving 1,950 hospitalized COVID-19 patients in Madrid showed that one year after discharge, the prevalence of post-COVID-19 cough was as low as 2.5%. However, in that study, only 28.1% of patients had cough at hospital admission (26) which was much lower than that in our study (79%) and other studies in China (8,(32)(33)(34)(35). Compared with studies from European and American countries, the prevalence of post-COVID-19 cough in Asian countries seemed to be lower (20-41.9% vs. 27.5-29%) (20)(21)(22)(23)(24)(25)(26)(27)36).…”
Section: Discussioncontrasting
confidence: 87%
“…A recent study involving 1,950 hospitalized COVID-19 patients in Madrid showed that one year after discharge, the prevalence of post-COVID-19 cough was as low as 2.5%. However, in that study, only 28.1% of patients had cough at hospital admission (26) which was much lower than that in our study (79%) and other studies in China (8,(32)(33)(34)(35). Compared with studies from European and American countries, the prevalence of post-COVID-19 cough in Asian countries seemed to be lower (20-41.9% vs. 27.5-29%) (20)(21)(22)(23)(24)(25)(26)(27)36).…”
Section: Discussioncontrasting
confidence: 87%
“…They reported physical symptoms such as tiredness, increased temperature, dizziness, throat irritation, cough, and dyspnea, as well as psychological symptoms such as difficulty concentrating, discomfort, and anxiety. Their physical symptoms matched the typical symptoms reported earlier in China by Wang et al (2020). Fever, cough, fatigue, myalgia, diarrhea, and headache were common symptoms at the beginning, worsening to dyspnea, hypoxia, leukopenia, lymphocytopenia, and neutropenia.…”
Section: Discussionsupporting
confidence: 76%
“…( Aghdam et al, 2020 , Jiehao et al, 2020 , Perrone et al, 2020 Nov 6 , Piersigilli et al, 2020 , Qian et al, 2020 , Qiu et al, 2020 , Rahimzadeh et al, 2019 , Robbins et al, 2020 , See et al, 2020 , Shen et al, 2020 Jun , Cai et al, 2020 , Shi et al, 2020 , Sieni et al, 2020 , Silverstein, 2016 , Sinelli et al, 2020 , Smargiassi et al, 2020 , Song et al, 2020 , Steinberger et al, 2020 , Sun et al, 2020 , Tan et al, 2020 , Tang et al, 2020 , Tang et al, 2020 , Urbankowska et al, 2015 Sep , Volpicelli and Francisco, 2009 , Carrabba et al, 2020 , Volpicelli and Gargani, 2020 Apr 21 , Wang et al, 2020 , Wang et al, 2020 , Wang et al, 2020 , Wang et al, 2020 , Wang et al, 2020 , WHO 2018 , Chan et al, 2020 , WHO 2020 , WHO 2020 , World Health Organization (WHO) 13 March 2020 , Influenza et al, 2009 , Wu et al, 2020 , Wu and McGoogan, 2020 , Xia et al, 2020 , Xie et al, 2020 , Xing et al, 2020 , Chang et al, 2020 , Xu et al, 2020 , Xu et al, 2020 , Xu et al, 2020 , Yin et al, 2020 , Yu et al, 2020 , Yu et al, 2020 , Zeng et al, 2020 , Zeng et al, 2020 , Chen et al, 2020 Apr 6 , Zhang et al, 2020 , Zhang et al, 2020 , Zhang et al, 2020 , Zhang et al, 2020 ,…”
Section: Uncited Referencesmentioning
confidence: 99%